The Morning After : The Impact on Collateral Supply After a Major Default - Turing, Dermot (IMF Working Papers; Working Paper, 2018)
Changes to the regulatory system introduced after the financial crisis include not only mandatory clearing of OTC derivatives at central counterparties and margining of uncleared derivatives, but also prudential measures, including notably a 'Liquidity Coverage Ratio' which obliges firms to set aside high-quality liquid assets (HQLA) as a stopgap against anticipated cash outflows. We examine factors which may affect the demand for HQLA in a severely stressed market following a hypothetical default of a major clearing member. Immediately following a major default, the amount of HQLA demanded by the whole market would spike. We estimate the size of the spike and draw conclusions as to whether the depth of the market is adequate to absorb it.